DESAIN KONSEP TANGKI PENAMPUNG BAHAN BAKAR PASSIVE COMPACT MOLTEN SALT REACTOR - Hadiwinata, A.; Widiharto, A.; Sihana (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The Passsive Compact Molten Salat Reactor (PCMSR) reactor is developed from MSR reactor. The PCMSR reactor design requires special place to temporarily storage for reactor fuel when incident occurs, such as when there is an accident which caused the temperature of the fuel increases. The tank consist of three interconnected parts, the reservoir liquid fuel, chimney, and the heat exchanger. In this research, the tank system is modeled based on a lump model and with variation of the initial power and height of chimney. Model boundary conditions set at the maximum fuel temperature of 1400°C, which is based on the molten salt LiF-BeF2-ThF4-UF4. In this analysis, calculation of pressure drop and heat transfer are conducted for 1800-3000 MWth and for chimney height variations were analyzed at height of 1-10 m. Results show that the larger power in reactors, the fuel tank height and the height of heat exchanger equipment required will be greater, increasing cooling fluid temperature and air temperature, increasing cooling fluid mass flow rate while the air mass flow rate decreases. Increasing the height of chimney causes height of the fuel tank and the height of the required heat exchanger decreases, decreasing coolant fluid temperature, but the air temperature will increase, causing cooling fluid mass flow rate will increase but the air mass flow rate will decrease.